Characterizing the regulatory effects of H2A.Z and SWR1-C on gene expression during hydroxyurea exposure in Saccharomyces cerevisiae. - Hilary T Brewis; Peter C Stirling; Michael S Kobor (PLoS Genetics)
Chromatin structure and DNA accessibility are partly modulated by the incorporation of histone variants. H2A.Z, encoded by the non-essential HTZ1 gene in S. cerevisiae, is an evolutionarily conserved H2A histone variant that is predominantly incorporated at transcription start sites by the SWR1-complex (SWR1-C). While H2A.Z has often been implicated in transcription regulation, htz1Δ mutants exhibit minimal changes in gene expression compared to wild-type. However, given that growth defects of htz1Δ mutants are alleviated by simultaneous deletion of SWR1-C subunits, previous work examining the role of H2A.Z in gene expression regulation may be confounded by deleterious activity caused by SWR1-C when missing its H2A.Z substrate (apo-SWR1-C). Furthermore, as H2A.Z mutants only display significant growth defects in genotoxic stress conditions, a more substantive role for H2A.Z in gene expression may only be uncovered after exposure to cellular stress. To explore this possibility, we generated mRNA transcript profiles for wild-type, htz1Δ, swr1Δ, and htz1Δswr1Δ mutants before and after exposure to hydroxyurea (HU), which induces DNA replication stress. Our data showed that H2A.Z played a more prominent role in gene activation than repression during HU exposure, and its incorporation was important for proper upregulation of several HU-induced genes. We also observed that apo-SWR1-C contributed to gene expression defects in the htz1Δ mutant, particularly for genes involved in phosphate homeostasis regulation. Furthermore, mapping H2A.Z incorporation before and after treatment with HU revealed that decreases in H2A.Z enrichment at transcription start sites was correlated with, but generally not required for, the upregulation of genes during HU exposure. Together this study characterized the regulatory effects of H2A.Z incorporation during the transcriptional response to HU.